Two decades of experience in explantation and graft preserving strategies following primary endovascular aneurysm repair and lessons learned - Sultan, Sherif; Acharya, Yogesh; Hezima, Mohieldin; Chua Vi Long, Keegan; Soliman, Osama; Parodi, Juan; Hynes, Niamh (Frontiers in Surgery, 2022)
Objectives: We aim to scrutinize our evolving re-intervention strategies following primary endovascular aortic aneurysm repair (EVAR) - EVAR GORE SalvAge Fabric Technique (ARAFAT), aortic sac double breasting with endograft preservation, and stent-graft explantation. Methods: We performed 1555 aortic interventions over the study period, including 910 EVARs. Factors associated with the need for reintervention and the likelihood of chronic fabric fatigue failure (CFFF) were investigated. Using conventional and innovative diagnostic modalities with Prone contrASt enHanced computed tomography Angiography (PASHA), 136 endoleaks (ELs) were identified (15 type I, 98 type II; 18 type III; 5 type IV). Results: Forty-four (4.84%) patients underwent re-intervention post-primary EVAR; 18 ARAFATs, 12 double breastings, and 14 explantations. Choice of re-intervention was based on patient fitness and mode of failure. Mean EL detection duration following primary EVAR was 53.3±6.82 months, while mean time to re-intervention was 70.20±6.98 months. The mean sac size before the primary EVAR and re-intervention was 6.00±1.75 cm and 7.51±1.94 cm, respectively. Polyester (61.40%) was the most commonly employed stent-graft material. Use of more than three modular stent-graft components (3.42±1.31, p=.846); with the proximal stent-graft diameter of 31.6±3.80 cm (p=.651) and the use of iliac limbs more than 17mm (p=.364), all added together are contributing factors. We had one peri-operative mortality following explantation due to sepsis-induced multiorgan failure. Conclusions: Our re-intervention strategies matured from stent graft explantation to graft preservation with endovascular relining of the stent-graft. Graft preservation with aortic sacotomy and double breasting were used to manage concealed ELs due to aortic hygroma.